2021
DOI: 10.3390/fermentation8010011
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation Condition and Quality Evaluation of Pineapple Fruit Wine

Abstract: This research investigated the impact of the concentration of pineapple juice on the characteristics of pineapple wine during fermentation with Saccharomyces cerevisiae var. burgundy. Three ratios of fresh pineapple juice to water were mixed to obtain three treatments, which were T1—2:1, T2—1:1, and T3—1:2. The °Brix and pH of all pineapple juice and water ratios were adjusted to 25 and 4, respectively. The results showed that changes in alcohol, pH, Total Soluble Solids (TSS), Total Titratable Acidity (TAA, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The antioxidant activity of plum wine in this study was similar to foreign red and white wines; specifically, plum wine indicated the same level of antioxidant activity as white wine which ranged from 152.7 to 445.52 µg TE/g [ 22 ]. Moreover, the TP content and antioxidant activity in plum wine depend on several factors, including variety and the winemaking process [ 21 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant activity of plum wine in this study was similar to foreign red and white wines; specifically, plum wine indicated the same level of antioxidant activity as white wine which ranged from 152.7 to 445.52 µg TE/g [ 22 ]. Moreover, the TP content and antioxidant activity in plum wine depend on several factors, including variety and the winemaking process [ 21 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…106 Moreover, this initial pre-treatment is also accompanied by an increase of PET surface roughness which has been exploited to produce PET fabrics with antimicrobial finish. 120 Selective partial hydrolysis of mixed blends is also a way to favor further selective enzymatic degradation, 121,122 or to produce Janus superhydrophobic PET textiles with uneven wetting properties. 123 3.4.5 Use of additives and catalysts.…”
Section: Hydrolysis In Alkaline Mediamentioning
confidence: 99%
“…Terephthalic acid (TPA) can be precipitated by adjusting the aqueous phase pH. 121 However, the separation of TPA and EG was not considered in this study.…”
Section: Enzymatic Pet Depolymerisationmentioning
confidence: 99%
“…Then, it was transferred to a fermentation tank and mixed with a starter of inoculum yeast cultures (5% v/v) at the working volume of 15 L. Fermentation was conducted for 10 days at 30 • C to obtain pineapple wine with a 10% v/v ethanol content. This proper fermentation process for pineapple wine used in this study was obtained from our previous study [39]. Thereafter, the alcohol fermentation was stopped and the pineapple wine was stored at 4 • C to be used as a raw material for pineapple vinegar fermentation.…”
Section: Pineapple Wine Fermentationmentioning
confidence: 99%